Determinants of Banking Profitability Listed on The Indonesia Stock Exchange Before and During Covid-19 - Rodyah Widyarini; Bambang Santoso Marsoem (Jurnal Syntax Admiration, 2021)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Operational Efficiency (BOPO), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL) and Covid-19 on profitability of  banking companies listed on Indonesia Stock Exchange (IDX during 2019 quartal 2 to 2021 quartal 1. While, from the population of 45 companies, it took 36 companies as sample. The study utilized panel data obtained from the  financial reports listed in banking listed in IDX. By using Fixed Effect Model, The results are CAR, NIM, LDR and Covid-19 had no effect on ROA. BOPO and NPL had a negatif and significant effect on ROA. Prediction capability from these six variables toward ROA is 93.41%. Meanwhile, the remaining 6,59% is explained by other factors outside the model